Artificial Intelligence in Academic Translation: A Comparative Study of Large Language Models and Google Translate - Мохаммед Мохсен (Психолінгвістика, 2024)
Purpose. The advent of Large Language Model (LLM), a generative artificial intelligence (AI) model, in November 2022 has had a profound impact on various domains, including the field of translation studies. This motivated this study to conduct a rigorous evaluation of the effectiveness and precision of machine translation, represented by Google Translate (GT), in comparison to Large Language Models (LLMs), specifically ChatGPT 3.5 and 4, when translating academic abstracts bidirectionally between English and Arabic.